A STUDY OF EMOTIONAL EMPATHY AND DELINQUENCY - Shazia Ashraf; Shazia Khalid; Firoza Ahmed (European Scientific Journal, ESJ, 2014)
In their study of personality and delinquency, psychologists have tried to understand the developmental trajectories leading to an antisocial youth. It has been noted that affective arousal in response to others in distress can promote interpersonal responsibility and inhibit harmful acts. It follows that deficits in the capacity to emotionally empathize would be related with delinquent acts, which may have harmful consequences for others.The present study investigated the relation of emotional empathy with delinquency in adolescent boys. The study was conducted on a sample of 125 adolescent boys, with an average age of 16.9 years, S.D. = 1.8 (ages ranging from 16 to 18 years). Participants were administered the Emotional Empathy Scale (EES) (Ashraf, 2004) and the Urdu translated version of Self- Reported Delinquency Scale (SRDSG). which was originally developed by Gibson (1971). Following hypotheses were tested: (a) Emotional empathy will be negatively correlated with delinquency, and (b) EES subscales will be negatively correlated with SRDSG scale. Consistent with expectation, a significant negative correlation coefficient of -.28 (p< .001) was obtained between the scales of EES and SRDSG. In addition, all EES subscales were also found to be significantly and inversely correlated with delinquency (ranging from r = .21 to -.29, p <.001). The negative relation found between the two scales supports the notion that affective empathy inhibits delinquent actions towards others.